Assessing the competitiveness and comparative advantage of broiler production in Johor using policy analysis matrix - Ahmed Awad, Elsedig Elbadawi; Ismail, Mohd Mansor; Mohamed Arshad, Fatimah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Malaysian poultry policy aims to provide remunerative prices for producers and to guarantee a steady supply of poultry products at stable and affordable prices to consumers. Broiler meat is the most important and the cheapest protein source in Malaysia and trade protection could stimulate the local industry and enhance food security. The study attempts to evaluate the competitiveness and comparative advantage of three different scales of broiler production in Johor using policy analysis matrix (PAM). The existing protection and the level of comparative advantage are ascertained through PAM indicators. The results show that Malaysia has strong competitiveness position in every scale of broiler production especially the largest scale. But, the protection through import curtailment resulted in higher domestic prices than the world price. To increase competitiveness, the broiler industry should reduce the dependence on expensive and unstable cost of corn based feed.